The Influence of Price and Product Quality on Purchase Decisions at Meimei Plaza Marelan - Ahmad Fadli (IHSA Institute, 2022)
The main study of this study is to analyze the effect of price and product quality on the purchasing decision of Meimei Plaza Marelan. The research approach is quantitative. The population in the study are customers who have used Vivo cellphones as many as 100 respondents. The sources of data in this study are primary data and secondary data. Where the primary data is from observations, interviews, and questionnaires. The results of the t test show that the price has a positive and significant effect on consumer purchasing decisions and the product quality variable also has a positive and significant effect on purchasing decisions. The most powerful variable in influencing purchasing decisions is price. The results of the coefficient of determination with a correlation regression value of 0.760, meaning that together the price and quality of the product on the purchasing decision of Vivo Mobile at Meimei Plaza Marelan have a close and positive contribution. Then the coefficient of determination (R2) is 0.760 (76%). So it can be said that 76% of the variation in the dependent variable, namely price and product quality in the model, can explain the purchasing decision variables at Meimei Plaza Marelan, while the remaining 24% is influenced by other variables outside the model.